Nonlinear Optical Rectification and Second Harmonic Generation in 2D Quantum Rings under Electric Field and Magnetic Fields (2014)
ABSTRACT: By using the effective mass and parabolic band approximations, the nonlinear optical rectification and the second harmonic generation are calculated in a two-dimensional quantum ring under the simultaneous effects of perpendicularly applied magnetic field and in-plane applied electric field. The geometry of the ring is modeled via the combined influences of a parabolic and inverse square confining potentials. The exact solutions for the two-dimensional motion of the conduction band electrons are used as the basis for a perturbation-theory treatment of the static electric field effect. The variation of one of the different potential energy parameters, for a fixed configuration of the remaining ones, leads to either blueshifts or redshifts of the resonant peaks as well as to distinct rates of change for their amplitudes.